ENGLISH READING MISCUE ANALYSIS ON AUTISTIC SPECTRUM DISORDER (ASD) STUDENTS AT THE INCLUSIVE SCHOOL GALUH HANDAYANI SURABAYA: A CASE STUDY - ASTIWIDYA, VIRANDHA DEA AYU (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Reading, Miscue Analysis, Retrospective Miscue Analysis (RMA), Autistic Spectrum Disorder (ASD), Inclusive School Galuh Handayani Surabaya. Reading habit potentially grants a big contribution in increasing human knowledge. Reading is necessary to be improved since it is trusted as a window of world knowledge which aims to gain the insight source. Miscue analysis is used as a guidance that can encourage the reader to manage his or her own reading development ability. The instructions on Retrospective Miscue Analysis (RMA) comprising reading text aloud, retelling and discussion session are used in the study since it intensively contributes to the readers in developing their reading skill. This study purports, first, to find out miscues types and second, to identify the factors contributing the miscue production by college Autistic Spectrum Disorder (ASD) students at the inclusive school Galuh Handayani Surabaya.In drawing the trustworthy results, the writer applied RMA theory (1969) and Kern’s theory (1988). The study was designed by using qualitative approach and a case study in order to gain more comprehensive and detail results. In collecting the data, the writer selected two ASD students with Asperger types who were qualified to participate in the study. The data were originated from all utterance of two participants while doing all activities in RMA procedure which are taken on recording process, and then they are transformed into transcription.The students made 129 miscues consisting of six types of miscues. Those miscues were 62 (48%) omissions, 46 (36%) substitutions, 10 (8%) selfcorrections, 5 (4%)reversals, 4 (3%) insertions, 2 (1%) repetitions. The results of factor identificationshowed linguistic, affective and cognitive factors as the three main factors contributingmiscue production. The results of the study showed that even good reader at the level of autism made miscues. Eventually, the finding could not be generalized as the whole case for autism.The writer recommends the next writer who wants to conduct a study in a similar concentration to examine different subjects using RMA based on various facets.